Magnesium Oxide nanoparticle effect on the growth, development, and microRNAs expression of Ananas comosus var. bracteatus. Issue 1 (1st January 2021) - Owusu Adjei, Mark; Zhou, Xuzixin; Mao, Meiqin; Xue, Yanbin; Liu, Jiawen; Hu, Hao; Luo, Jiaheng; Zhang, Huiling; Yang, Wei; Feng, Lijun; Ma, Jun
ABSTRACT: The use of nanoparticles in the appropriate portion to increase plant growth and development is an ongoing biological process. However, its exposure in an inconsiderable proportion become stressful and plant uses diverse regulatory mechanisms such as gene expression and miRNAs regulation to attain their cellular homeostasis. This study documented the influence of MgO NPs on genes and miRNAs expression, cell morphology, chlorophyll content, and physiological changes in Ananas comosus var. bracteatus at different treatment levels. It's found that as MgO NPs exposed to the plant's increased, the average root length, average biomass, and average leaf length significantly decreased. A low concentration of MgO NPs (1 g/mL) increased the chlorophyll content of leaves, while 2 and 4 g/mL decreased it significantly. A 4 g/mL of MgO NPs increased the expression of miR-396 and miR-398 extremely, while repressed the expression of RHS12 and XTH genes significantly. Furthermore, the number of vascular bundles of root stele decreased obviously under 4 g/mL MgO NPs. 20 nm MgO NPs may have a destructive influence on the growth and development of Ananas comosus var. bracteatus by inhibiting chlorophyll.